2000
DOI: 10.1002/1096-8628(20000918)94:3<237::aid-ajmg10>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Familial mandibuloacral dysplasia: Report of an additional Italian patient

Abstract: Mandibuloacral dysplasia is a rare condition. Only 11 families have been reported and five of them were Italian, while consanguinity was found only in one report. We describe an additional Italian patient born from consanguineous parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…2,7 In this case, the presentation of consanguineous parents and the history of an affected sibling with similar physical characteristics strengthens the data suggesting that MAD has an autosomal recessive trait. 2,7-10 Only two out of the eleven previously reported families with MAD were determined to be consanguineous.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…2,7 In this case, the presentation of consanguineous parents and the history of an affected sibling with similar physical characteristics strengthens the data suggesting that MAD has an autosomal recessive trait. 2,7-10 Only two out of the eleven previously reported families with MAD were determined to be consanguineous.…”
Section: Discussionsupporting
confidence: 72%
“…2,7-10 Only two out of the eleven previously reported families with MAD were determined to be consanguineous. 2,3 We believe that this case, where the parents of the patient were first-degree cousins, will add to the data on consanguinity. However, since consanguineous marriages in Turkey have a relatively high incidence, 11 the association may be considered coincidental.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that there is a specific genotype-phenotype correlation between the R527H mutation and MADA (Novelli et al, 2002;Shen et al, 2003). Previous studies also postulated that only MADA is caused by R527H and that there is a correlation between the R527H mutation and lipodystrophy pattern (Tudisco et al, 2000;Simha et al, 2003). LMNA gene homozygous R527H or A529V or A529T mutations have been reported in MADA.…”
Section: Resultsmentioning
confidence: 52%
“…It was believed that hyperglycemia in heterozygous carriers might have been related to a heterozygous LMNA Ala529Val mutation. According to several studies, lipodystrophy and metabolic findings of insulin resistance such as diabetes mellitus and hypertriglyceridemia have also been reported in some patients with the LMNA mutation (Tudisco et al, 2000;Simha and Garg, 2002). Further studies are required to confirm the relationship between LMNA mutations, insulin resistance, and hyperglycemia.…”
Section: Resultsmentioning
confidence: 71%